Penegakan Hukum Terhadap Pelaku Residivis Tindak Pidana Pencurian - Moh. Elson I.M.Tandesa; Moh. Rusdiyanto U. Puluhulawa; Apripari Apripari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to find out how law enforcement is carried out against perpetrators of recidivist criminal acts of theft. The research method used is juridical-normative which is analyzed qualitatively. The research results show that recidivism is the repetition of a criminal act by the same perpetrator, where the criminal act committed previously has been sentenced to a criminal sentence and has permanent legal force, and the repetition occurs within a certain period of time. When imposing a sentence, the judge does not mention the amount of additional prison sentence of 1/3 (one third) of the main criminal threat (the presence of a criminal aggravation due to recidivism reasons), because the judge will basically immediately impose a long sentence on the defendant. Crime prevention is a variety of proactive and reactive activities directed at perpetrators and victims, and in the social and physical environment, carried out before and after a crime occurs. There are two ways of dealing with recidivist crimes, namely, preventive and repressive.